Deciphering immune cell interaction aberrations in necrotizing enterocolitis: the regulatory role of DHRS7 - Gao, Kexin; Chen, Yuehua; Lu, Jingjing; Ge, Wenliang; Yin, Qiyou (Frontiers in Immunology, 2026)
BackgroundNecrotizing enterocolitis (NEC) is a severe inflammatory condition predominantly affecting preterm infants and is one of the leading causes of neonatal mortality worldwide. Despite its significant impact, the pathogenesis of NEC remains unclear, particularly regarding the role of aberrant immune cell responses and uncontrolled inflammation. This study aimed to investigate how dehydrogenase/reductase 7 (DHRS7), a protein potentially influencing immune cell function and inflammatory signaling pathways, contributes to the development of NEC.MethodsScreening and analyzing differential proteins between normal samples and NEC samples through proteomic sequencing. Bioinformatics analyses of the GSE46619 dataset were performed, including differential expression profiling, receiver operating characteristic (ROC) curve analysis for diagnostic efficacy, gene set enrichment analysis (GSEA) for pathway enrichment, and cell-type identification by estimating relative subsets of RNA transcripts (CIBERSORT) to evaluate immune cell infiltration. Gene interactions and functional pathways were further explored using gene multiple association network integration algorithm (GeneMANIA), KEGG and GO analyses. Molecular docking studies were conducted to investigate the binding interactions of DHRS7 with small molecules. A murine model of NEC was established to evaluate inflammatory responses through Hematoxylin and eosin (H&E) staining and immunofluorescence, as well as to assess DHRS7 expression using immunohistochemistry. Additionally, lipopolysaccharide (LPS)-stimulated rat IEC-6 cells served as an in vitro model, with DHRS7 expression levels and inflammatory cytokines quantified using RT-qPCR and western blot.ResultsProteomic sequencing and bioinformatics analysis revealed that DHRS7 was significantly downregulated in NEC tissues and could serve as a diagnostic marker. GSEA enrichment analysis indicated a strong association between DHRS7 and inflammatory signaling pathways. Moreover, immune profiling showed an increase in neutrophil and macrophage infiltration in tissues with low DHRS7 expression. DHRS7 demonstrated a high affinity for mitogen-activated protein kinase (MEK) inhibitor small molecules. Additionally, DHRS7 expression was markedly reduced in both NEC mouse models and LPS-induced IEC-6 cells.ConclusionDHRS7 is significantly downregulated in NEC tissues, potentially serving as a diagnostic marker, while its decreased expression is associated with increased neutrophil and macrophage infiltration, underscoring its vital role in immune modulation in NEC.